Pengaruh sistem nilai budaya kaum ningrat Jawa terhadap kehidupan seni tari keraton Yogyakarta : laporan penelitian - Pujasworo, Bambang (Akademi Seni Tari Indonesia Yogyakarta, Departemen Pendidikan dan Kebudayaan, 1984)
On the influence of the cultural values of the Javanese aristocracy on the life of the traditional dance performers of the Kraton Yogyakarta.